Intellectual collaboration with the Third Reich : treason or reason? - Björkman, Maria 1974- HerausgeberIn; Lundell, Patrik 1969- HerausgeberIn; Widmalm, Sven 1956- HerausgeberIn (Routledge studies in Second World War history, 2019)
"The book investigates the rather neglected "intellectual" collaboration between National Socialist Germany and other countries, including views on knowledge and politics among "pro-German" intellectuals, using a comparative approach. These moves were shaped by the Nazi system, which viewed scientific and cultural exchange as part and parcel of their cultural propaganda and policy. Positive views of the Hitler regime among intellectuals of all sorts were indicative of a broader discontent with democracy that, among other things, represented an alternative approach to modernization which was not limited to the German heartlands. This book draws together international experts in an analysis of right-wing Europe under Hitler; a study which has gained new resonance amidst the wave of European nationalism in the twenty first century"--